Temporal trend of mortality from Multiple Sclerosis in Brazil by sex, ethnicity, and age group, between 2001 and 2022 (Research, Society and Development, 2025)
Introduction: Multiple sclerosis (MS) is the most prevalent demyelinating disease of the central nervous system (CNS). It is estimated to affect approximately 2 to 2.5 million people globally, with higher prevalence in women and a peak incidence around 30 years of age. Objective: This study aims to analyze the temporal trend of MS mortality rates in Brazil between 2001 and 2022, stratified by sex, ethnicity, and age group. Methods: This is an ecological time-series study of MS mortality rates in Brazil, stratified by sex, ethnicity, and age group. Mortality data were collected from the Department of Informatics of the Unified Health System (DATASUS), in the Mortality Information System (SIM) section. Results: A total of 6,848 deaths were reported in Brazil between 2001 and 2022. Women accounted for most deaths (60.48%). White individuals had the highest mortality rate (66.41%), followed by brown/mixed (23.41%) and black individuals (5.10%). Mortality was higher in older age groups, with 28.8% of deaths occurring in individuals over 70 years old, possibly reflecting the impact of associated comorbidities. Conclusion: This study revealed a relatively low MS mortality rate compared to countries with predominantly Caucasian populations. The findings corroborate previous research, showing higher MS mortality among women, white individuals, and older adults. The national trend indicates stability in MS mortality.